Relationship Between Isokinetic Lower-Limb Joint Strength, Isometric Time Force Characteristics, and Leg-Spring Stiffness in Recreational Runners - Chen, Shiqin; Wang, Dan; Zhang, Qin; Shi, Yue; Ding, Haiyong; Li, Fei (Frontiers in Physiology, 2022)
Neuromuscular characteristics, such as lower-limb joint strength and the ability to rapidly generate force, may play an important role in leg-spring stiffness regulation. This study aimed to investigate the relationship between isokinetic knee and ankle joint peak torque (PT), the force-time characteristics of isometric mid-thigh pull (IMTP), and leg stiffness (Kleg) /vertical stiffness (Kvert) in recreationally trained runners. Thirty-one male runners were recruited and underwent three separate tests. In the first session, the body composition, Kleg, and Kvert at running speed of 12 and 14 km·h-1 were measured. In the second session, isokinetic knee and ankle joint PT at 60°·s-1 were tested. The force-time characteristics of the IMTP were evaluated in the final session. Pearson’s product-moment correlations, with the Benjamini–Hochberg correction procedure, showed that the knee flexor concentric and eccentric, and extensor concentric PT (r = 0.473 to 0.654, p < 0.05) were moderately to largely correlated with Kleg and Kvert at 12 and 14 km·h-1. The knee extensor eccentric PT (r = 0.440, p = 0.050) was moderately correlated with the 14 km·h-1 Kvert. The ankle plantar flexor concentric and dorsiflexor eccentric PT (r = 0.506 to 0.571, p < 0.05) were largely correlated with Kleg at 12 km·h-1. The ankle plantar flexor concentric and eccentric, and dorsiflexor eccentric PT (r = 0.436 to 0.561, p < 0.05) were moderately to largely correlated with Kvert at 12 and 14 km·h-1. For IMTP testing, high correlation was only found between the IMPT PF and Kvert at 14 km·h-1 (r = 0.510, p = 0.014). Thus, superior leg-spring stiffness in recreational runners may be related to increased knee and ankle joint strength, eccentric muscular capacity, and maximal force production.